Anesthetic Challenges of Extrinsic Trachea-bronchial Compression due to Posterior Mediastinal Mass: Our Experience with a Large Esophageal Mucocele - Tewari, Saipriya (Ann Card Anaesth, 2017)
Large posterior mediastinal masses may lead threatening complications such as critical tracheobronchial compression. Airway management in these individuals is a challenge and being a lower airway obstruction; rescue strategies are limited. We encountered one such case of a large esophageal mucocele causing extrinsic tracheobronchial compression. We have described the anesthetic management of this case using awake fiber-optic assessment followed by intubation. Close communication with the surgical team, meticulous planning of airway management, and early drainage of the mucocele are the cornerstones of management in such patients.